Republic of Yemen : City and Inter-City Land Transport Sector - Strategy Note - World Bank (World Bank, 2012)
The World Bank's study covered all modes of city and inter-city land transport, also designated in this report under the name of 'road transport'. However, the report focuses on the Governments two main concerns: the urban bus and taxi sector, which performs poorly and is a major cause of the growing traffic congestion in Yemeni cities, particularly in Sana'a; and the inter-city freight sector, which does not presently develop in ways that adequately serve the economy. Sana'a is indeed a large and fast growing city where public transport has become critical. Its population was 1.75 million in 2004, while forecasts are for 2.8 million for 2014 and 3.8 million for 2024. Yet, Sana'a's public transport system performs poorly. Similarly, the efficiency of inter-city freight transport is low and it does not promote trade, competition, and low price of basic commodities as it should. In addition, Yemen faces a very high rate of road accidents: in 2006, the number of recorded accidents was about 13,000, resulting in about 2,700 deaths and 18,000 injuries. The current legal framework for the regulation of city and inter-city transport is contained in law 33 of 2003 which created an open market for passenger and freight transport services, replacing the previous monopolies held by syndicates. Tariffs for road freight and passenger services are unregulated.